Randomised controlled trial of perinatal vitamin D supplementation to prevent early-onset acute respiratory infections among Australian First Nations children: the ‘D-Kids’ study protocol - Anne B Chang; Peter S Morris; Tom Snelling; Paul V Licciardi; Michael J Binks; David Simon; E Kim Mulholland; Adrienne Kirby; Heather D'Antoine; Amy S Bleakley; Susan J Pizzutto; Michelle Lamberth; et al. (BMJ Open Respiratory Research)
Introduction Globally, acute respiratory infections (ARIs) are a leading cause of childhood morbidity and mortality. While ARI-related mortality is low in Australia, First Nations infants are hospitalised with ARIs up to nine times more often than their non-First Nations counterparts. The gap is widest in the Northern Territory (NT) where rates of both acute and chronic respiratory infection are among the highest reported in the world. Vitamin D deficiency is common among NT First Nations neonates and associated with an increased risk of ARI hospitalisation. We hypothesise that perinatal vitamin D supplementation will reduce the risk of ARI in the first year of life.Methods and analysis ‘D-Kids’ is a parallel (1:1), double-blind (allocation concealed), randomised placebo-controlled trial conducted among NT First Nations mother–infant pairs. Pregnant women and their babies (n=314) receive either vitamin D or placebo. Women receive 14 000 IU/week or placebo from 28 to 34 weeks gestation until birth and babies receive 4200 IU/week or placebo from birth until age 4 months. The primary outcome is the incidence of ARI episodes receiving medical attention in the first year of life. Secondary outcomes include circulating vitamin D level and nasal pathogen prevalence. Tertiary outcomes include infant immune cell phenotypes and challenge responses. Blood, nasal swabs, breast milk and saliva are collected longitudinally across four study visits: enrolment, birth, infant age 4 and 12 months. The sample size provides 90% power to detect a 27.5% relative reduction in new ARI episodes between groups.Ethics and dissemination This trial is approved by the NT Human Research Ethics Committee (2018-3160). Study outcomes will be disseminated to participant families, communities, local policy-makers, the broader research and clinical community via written and oral reports, education workshops, peer-reviewed journals, national and international conferences.Trial registration number ACTRN12618001174279.